2017
DOI: 10.4081/ni.2017.7015
|View full text |Cite
|
Sign up to set email alerts
|

Somatoform dissociation, fatigue severity and pain behavior compared in patients with migraine headache and in healthy individuals

Abstract: The prevalence of migraine in the world is about 15 and 7% among women and men, respectively. The purpose of this study was comparison of somatoform dissociation, fatigue severity and pain behavior in patients with migraine headache and its relationship with coping strategies. This descriptive analytical study has been done on 120 patients with migraine headache and 120 healthy subjects were selected randomly. Data collected by somatoform dissociation questionnaire (SDQ-20), fatigue severity scale, pain behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We revealed that fatigue intensity in episodic migraineurs did not differ significantly from fatigue intensity in healthy individuals. Whereas in other similar studies levels of fatigue (including measured by FSS) were significantly higher in EM patients compared to healthy subjects [12,14]. Perhaps this difference is the result of social, demographic, comorbid and other characteristics of patients.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We revealed that fatigue intensity in episodic migraineurs did not differ significantly from fatigue intensity in healthy individuals. Whereas in other similar studies levels of fatigue (including measured by FSS) were significantly higher in EM patients compared to healthy subjects [12,14]. Perhaps this difference is the result of social, demographic, comorbid and other characteristics of patients.…”
Section: Discussionmentioning
confidence: 61%
“…In particular, we have demonstrated that post-stroke fatigue has specific qualitative and quantitative characteristics and specific predictors even depending on the timing after stroke [7][8][9]. In recent years, evidence has emerged that fatigue in migraine patients is different from fatigue in healthy people [10][11][12][13][14][15][16]. Moreover, fatigue prevalence and fatigue intensity in episodic migraine (EM) patients were significantly higher compared to patients with chronic migraine [15].…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates of at least one positive item under the PP domain of depression among CM than HS and among EM than HS. [59][60][61][62][63][64] These results are not new since the PP domain clusters with clinically relevant aspects, which are usually studied separately. However, the use of such domain might contribute in building a unitary disease concept 65 of migraine.…”
Section: Discussion Of the Results Based On The Literaturementioning
confidence: 99%